A4NH 2019 annual report highlights: Flagship 2 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
This includes three highlights document for Flagship 2 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Engaging the private sector Highlight 2: Reaching the most vulnerable Highlight 3: Research to inform action